2005
DOI: 10.1332/1744264053730752
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the evidence: reflections from experience

Abstract: English Evidence-based policy (EBP), along with the ‘systematic review’, has recently emerged as a prominent strand within social science and public policy research. A number of articles have heralded this emergence but the vast majority are theoretical and concerned with how EBP research could be practised. This article reflects on the author’s experiences of identifying and reviewing evidence on the effectiveness of labour market interventions aimed at people with a disability or a chronic illness, to demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…For example, in the two systematic reviews of shift work interventions, although 27 different databases were searched, 40 of the 66 included studies were found in either Medline or Embase, and half (13) of the others were found by citation follow-up (box 1). 17 18 Similarly, in the systematic review of welfare to work interventions, only three were located by electronic searches, with the rest found by specialist website searches and citation follow-up 14 21. Evidence from other reviews also supports the value of website searches and citation follow-up in locating new studies 36…”
Section: Conducting a Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, in the two systematic reviews of shift work interventions, although 27 different databases were searched, 40 of the 66 included studies were found in either Medline or Embase, and half (13) of the others were found by citation follow-up (box 1). 17 18 Similarly, in the systematic review of welfare to work interventions, only three were located by electronic searches, with the rest found by specialist website searches and citation follow-up 14 21. Evidence from other reviews also supports the value of website searches and citation follow-up in locating new studies 36…”
Section: Conducting a Reviewmentioning
confidence: 97%
“…It should define the intervention of interest, the population receiving the intervention, the outcome(s) of interested, and the study designs deemed worthy of inclusion 11. However, the use of systematic reviews in evaluating public health and social interventions has highlighted problems with this approach as policy or practice questions may well be broader and the answer may cover more than one intervention 21. For example, in the welfare to work review (box 1) the policy (or intervention) under review was ‘welfare to work’; however, this covers a multitude of different types of intervention (such as antidiscrimination legislation, vocational rehabilitation, return to work credits, etc), which may operate on the outcome in different ways 14.…”
Section: Conducting a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the criticisms, evidence-based approaches are now central to medical research and practice, and RCTs remain the gold standard, with qualitative research evidence still being viewed by many in the medical profession as poorer quality research. Evidence-based policy research became established in the late 1990s, seeking to provide evidence about the operation, impact, outcome and effectiveness of public policy interventions, for the purpose of informing public policy formulation and implementation (Bambra, 2005). Policies should be effective in their use of rationed resources, particularly time and finance (Davies and Smith, 1999;Macintyre and Petticrew, 2000;Campbell Collaboration, 2001).…”
Section: The Development Of Evidence-based Managementmentioning
confidence: 99%
“…Victora et al (2004) make a similar case in respect of evidence for public health interventions, arguing that evaluations of interventions in a variety of everyday settings accompanied by a plausible rationale for why the outcomes observed occurred, would better inform policy and practice than studies with the highest internal validity. Bambra (2005) highlights the difficulties inherent in attributing impact to specific policies (and thus their potential impact in other contexts) when the environment in which these policies are evaluated is already shaped by other policies that are themselves evolving. In a similar vein, Wallace et al (2006) point to the significant social and economic changes that can take place over time and which may confound external validity.…”
Section: Internal Versus External Validitymentioning
confidence: 99%